Safety Evaluation of Rockfill Dam Based on Seepage Discharge Data - Sulistya, Krisna; Sachro, Sri Sangkawati; Sukamta, Sukamta (Universitas Tribhuwana Tunggadewi Malang, 2023)
The leading cause of failure of an embankment dam is the occurrence of excessive seepage, which triggers piping that can disrupt the stability and safety of the dam. This study discusses the dam's safety against the danger of seepage with a case study of the Jatibarang Dam. The safety evaluation uses V-notch monitoring data during the operational period from 2018 to 2021. The highest seepage discharge recorded during that period was 2,232 lt/sec/m, where the unsafe threshold for seepage based on the dam's height was 0,56 lt/sec/m, so seepage is unsafe. Meanwhile, based on the seepage discharge index (QI) calculation, the QI value is less than one, so the seepage discharge is still safe. Evaluating dam safety against excessive seepage discharge for dams of the same type as the Jatibarang Dam is more appropriate to use the seepage discharge index (QI) threshold because the parameters in the equation are complete.ABSTRAKPenyebab utama kegagalan suatu bendungan tipe urugan adalah terjadinya rembesan berlebih yang memicu piping yang dapat mengganggu kestabilan dan keamanan bendungan. Penelitian ini membahas keamanan bendungan terhadap bahaya rembesan dengan studi kasus Bendungan Jatibarang. Evaluasi keamanan menggunakan data pemantauan V-notch selama masa operasional tahun 2018 sampai dengan 2021. Debit rembesan tertinggi yang tercatat pada kurun waktu tersebut sebesar 2,232 lt/dt/m, dimana ambang batas tidak aman terhadap rembesan berdasarkan ketinggian bendungan adalah 0,56 lt/dt/m sehingga rembesan dalam kondisi tidak aman. Sedangkan berdasarkan perhitungan indeks debit rembesan (QI) menghasilkan nilai QI kurang dari satu sehingga debit rembesan masih dalam kondisi aman. Evaluasi keamanan bendungan terhadap debit rembesan berlebih terhadap bendungan yang se-tipe Bendungan Jatibarang lebih tepat menggunakan ambang batas indeks debit rembesan (QI) karena parameter pada persamaannya lebih lengkap.